PENGEMBANGAN POTENSI DESA WISATA BERBASIS BUDAYATINJAUAN TERHADAP DESA WISATA DI JAWA TENGAH - Priyanto, Priyanto; Safitri, Dyah (Jurnal Vokasi Indonesia, 2016)
This study to unearth village tourism for culture attraction tourim and to show there are some basic problem for existence village tourism in Central Jawa. The methodology was used qualitative research method with descriptive analysis. The result of this stuy indicate that for general potential cultural village tourism in Central Java is many. The problems that for like human resource, infrastructure & facillity, promotion. The problems can be finish with active any other especialy the people from culture village tourism.